Avaliação da influência do dispositivo prateleira de luz no conforto visual em edificação comercial com entorno obstruído - Maioli, Ricardo Nacari (2014)
The use of daylight in the interior of buildings is fundamental when considering visual comfort and energy efficiency. However, the high brightness of the tropical sky in the work environment can provide to the user visual discomfort, heat, or both, caused by the intense brightness of the openings and the inner surfaces and the burden of excessive heat. The most common type of buildings observed in the country does not provide solutions to these problems, since its interior lighting is done via windows which provide a non-uniform lighting environment. In the tropics, the sun protection elements present themselves as good solutions to reduce the incidence of direct solar radiation in the openings and redirects light devices assist in a more uniform distribution in the environment. An architectural element that fulfills both functions is the lightshelf. Because urban centers continue to expand vertically, it is becoming more and more difficult to gain access to natural light, particularly on the first floor. Research aims to find a solution to the problem by trying to investigate the influence of light shelves on the use of natural light under conditions where surroundings are obstructed. Due to the large spatial extent of Brazil - which results in significant variations in the brightness of the region - the cutting of the object considered the performance of two types of glass combined with two geometries shelf light or its absence, in six different Brazilian latitudes and four different orientations for a given type of office building. The percentage of useful luminosity in environments during the year and the levels of luminance from the openings with the aid of software Daysim were investigated. The analyzed results show that the adoption of this device was effective in all directions, under conditions with surrounding obstruction, aiding in the reduction of glare on the internal surfaces and allowed standardization of natural light, providing greater visual comfort to the user.